Progressive Fatal Myelopathy Secondary to Isolated Spinal Cord Vasculitis - Fisher, Arie; Rahman, Habib; Farrell, Michael; Hennessy, Michael (Frontiers in Neurology, 2017)
A 56 year old woman with various neurological signs which developed over a one year period was admitted for evaluation. MRI showed a markedly abnormal signal in the cervical spine. Despite treatment with IV steroids she developed a progressive myelopathy, became quadriplegic and required intubation. Immunomodulatory treatment was ineffective. The patient died 24 days after admission. Histopathological investigation revealed spinal cord necrosis with a lymphocyte predominant meningovascular inflammation involving arteries and veins along with evidence of prior occlusive disease of the anterior spinal artery. The changes were confined to the spinal cord. The present case represents an unusual cause of myelitis for which early and aggressive immunomodulatory treatment may have influenced outcomes.